Mutu Layanan Pendidikan Di SMP Negeri 1 Mesuji - Hendro, (UNISAN JURNAL, 2024)
This research aims to analyze the quality of educational services at SMP Negeri 1 Mesuji by focusing on various aspects that influence the quality of educational services. The research method used is a qualitative method with a case study approach. Data was collected through observation, interviews and analysis of related documents, as well as using direct observation techniques in the field. Research respondents included teaching staff, students, parents and school administration staff. The research results show that the quality of educational services at SMP Negeri 1 Mesuji has several advantages, such as sufficient teacher competence, adequate facilities, and a curriculum that meets standards. However, there are also several weaknesses, such as a lack of training to improve teachers' teaching skills, a lack of availability of up-to-date teaching materials, and a lack of parental involvement in the education process. SWOT analysis is used to evaluate internal and external factors that influence the quality of educational services at SMP Negeri 1 Mesuji. Based on this analysis, recommendations are given to improve the quality of educational services, including by increasing training for teaching staff, developing a curriculum that is more relevant to student needs, strengthening collaboration with students' parents, and improving learning support facilities. This research contributes to the development of the quality of educational services at SMP Negeri 1 Mesuji and can be a reference for further research in the field of education to increase the effectiveness and efficiency of the education system at the secondary level.